Hubungan Tingkat Kesepian dengan Depresi pada Lansia Di UPTD Pusat Pelayanan Sosial Griya Lansia - Rahmawati, Ajeng Rizqia; Wisnusakti, Khrisna; Noch Bolla, Ibrahim (JURNAL KESEHATAN KARTIKA, 2023)
Getting old is marked by a biological decline that looks like the skin begins to loosen, reduced vision and hearing function, easily tired and susceptible to disease. In addition to physical changes, the elderly can experience changes in psychological terms which greatly affect the quality of life, such as getting senile, lonely, afraid of losing loved ones and loved ones, afraid of facing death, and experiencing depression. The purpose of this study was to identify a relationship between the level of loneliness and depression in the elderly at the UPTD Griya Elderly Social Service Center. The research design used an analytic survey with a cross-sectional approach. The sample in this study were the elderly who were at the UPTD Griya Elderly Social Service Center. The number of samples in this study were 66 elderly people, using purposive sampling. Data collection is done by filling out a questionnaire. Data analysis was performed univariately and bivariately with the Chi-square test. The results showed that from a total of 66 respondents, 31 respondents with low loneliness experienced mild depression as many as 26 respondents with a percentage of 83.9%. And 35 respondents with moderate loneliness experienced moderate depression as many as 24 respondents with a percentage of 68.6%. The statistical test results obtained a value (p value = 0.000), because the p value <0.05, it can be concluded that there is a significant relationship between the level of loneliness and depression in the elderly at the UPTD Griya Elderly Social Service Center. It is recommended that the caretaker of the orphanage can accompany and pay more attention to the elderly and routinely invite the elderly to make contact with the surrounding environment such as discussing or just chatting, and can develop what activities can be effective in anticipating things or behaviors that can cause loneliness and depression in the elderly.